Perspectives for Targeting Ezrin in Cancer Development and Progression - Jean Carlos Lipreri da Silva; Hugo Passos Vicari; João Agostinho Machado-Neto (MDPI AG, 2023)
Recent advances have been made in understanding molecular markers involved in cancer malignancy, resulting in better tumor staging and identifying new potential therapeutic targets. Ezrin (EZR), a member of the ezrin, radixin, moesin (ERM) protein family, is essential for linking the actin cytoskeleton to the cell membrane and participates in the signal transduction of key signaling pathways such as Rho GTPases and PI3K/AKT/mTOR. Clinical and preclinical studies in a wide variety of solid and hematological tumors indicate that (i) EZR is highly expressed and predicts an unfavorable clinical outcome, and (ii) EZR inhibition reduces proliferation, migration, and invasion in experimental models. The development of pharmacological inhibitors for EZR (or the signaling mediated by it) has opened a new round of investigation, but studies are still limited. The scope of the present review is to survey studies on the expression and clinical impact of EZR in cancer, as well as studies that perform interventions on the function of this gene/protein in cancer cells, providing proof-of-concept of its antineoplastic potential.